Global existence and blow-up of a Petrovsky equation with general nonlinear dissipative and source terms - Mosbah Kaddour; Farid Messelmi (université de msila, 2023)
This work studies the initial boundary value problem for the Petrovsky equation with nonlinear damping ∂ 2u ∂t2 + ∆2 u − ∆u 0 + |u| p−2 u + αg
Keywords: Global existence, blow-up, nonlinear source, nonlinear dissipative, Petrovsky equation.